THE PROBLEM OF PLASTIC ANATOMY IN THE COMPLEX STUDY OF THE FORMATIVE PROCESS BY STUDENT WORKERS IN THE CLASSES OF DECORATIVE-APPLIED - M.M. Kryzhanivsky (Academy of Cognitive and Natural Sciences, 2009)
In the article rasmatrivaetsya problem of application of plastic anatomy in complex study to the formoobrazovatel'nogo process of studentami - trudovikami on employments of fine art. It is rotined that forming of graphic skills and abilities considerably depends on knowledges the students of plastic anatomy.